Návrh na zlepšení marketingového řízení ve vinařské firmě - Drtilová, Alena (Vysoké učení technické v Brně. Fakulta podnikatelská, 2009)
Diplomová práce se zabývá analýzou problémů, které souvisejí s marketingovým řízení vinařské firmy. Obsahuje zhodnocení současného stavu firmy a návrh na zlepšení marketingové strategie, která povede ke zlepšení propagace a distribuce firmy a k upevnění postavení na trhu

Master´s thesis deals with analysis of issues related to the marketing management of the viticultural company. Includes an assessment of the current state of the company and a proposal to improve marketing strategies that will improve the promotion and distribution company and strengthening market position.
Suggestion to Improve Marketing Strategy of the Viticultural Company
Keywords: Distribuce; marketingové prostředí; propagace; marketingový mix; SWOT analýza; zákazník; konkurence.; Distribution; marketing environment; promotion; marketing mix; SWOT analysis; customer; competition.